2018
DOI: 10.23917/forgeo.v32i1.5882
|View full text |Cite
|
Sign up to set email alerts
|

Land Subsidence Analysis of Reclaimed Land using Time-Lapse Microgravity Anomaly in Manado, Indonesia

Abstract: Coastal area land reclamation is a policy with various benefits, including its potential to increase economic growth. However, reclamation also potentially has adverse impacts on the environment, including increasing pressure on biodiversity, natural resources and natural ecosystems, and the most common problem is land subsidence. This study uses time-lapse microgravity anomaly to ascertain the distribution of gravity and vertical gradient anomaly in order to map the subsidence characteristics occurring in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The main factor that influences the measurement of the vertical gradient gravity method is the free air factor because in the measurement process this method requires two measurements at one measurement point location. The first measurement is carried out above the ground or the height of the gravimeter is close to 0 cm, then at the same point the second measurement is carried out by lifting the gravimeter with a tripod at a certain height [9]. The scheme for measuring the gravity of the vertical gradient can be seen in Figure 1.…”
Section: Gravity Methodsmentioning
confidence: 99%
“…The main factor that influences the measurement of the vertical gradient gravity method is the free air factor because in the measurement process this method requires two measurements at one measurement point location. The first measurement is carried out above the ground or the height of the gravimeter is close to 0 cm, then at the same point the second measurement is carried out by lifting the gravimeter with a tripod at a certain height [9]. The scheme for measuring the gravity of the vertical gradient can be seen in Figure 1.…”
Section: Gravity Methodsmentioning
confidence: 99%
“…A simple Bouguer anomaly contour map in the January and June 2019 periods is shown in FIGURE 7 below. Based on theoretical studies [12], [13], the results of modeling and contour of gravity data, in general, are interesting is the intermittent microgravity anomaly, not the value of gravity for each period. In each period, we only know the value (quantity) and have no physical artist at that time.…”
Section: Gravity Measurement Value (G Obs )mentioning
confidence: 99%
“…As an area located on the coast and directly bordering the Pacific Ocean, North Sulawesi is vulnerable to coastal flooding, especially in Manado City. Wibowo et al (2018) found that the Manado reclamation area experienced land subsidence and groundwater levels. This is in line with research by Triana & Janottama (2021) which projected that Manado, along with other coastal cities in Southeast Asia, will experience a higher rate of sea level rise than the global average.…”
Section: Introductionmentioning
confidence: 99%